Jianpi Jieyu Decoction, An Empirical Herbal Formula, Exerts Psychotropic Effects in Association With Modulation of Gut Microbial Diversity and GABA Activity - Liu, Lanying; Zou, Zhilu; Yang, Jiangwei; Li, Xiaoqi; Zhu, Boran; Zhang, Hailou; Sun, Yan; Zhang, Yuxuan; Zhang, Zhang-Jin; Wang, Wei (Frontiers in Pharmacology, 2021)
Background: Recent studies suggest that gut microbiota was associated with the bidirectional gut-brain axis which could modulate neuropsychological functions of the central nervous system. Gut microbiota could produce gamma aminobutyric acid (GABA) that could modulate the gut–brain axis response. Jianpi Jieyu (JPJY) decoction, a traditional Chinese formula, is mainly composed of Astragalus membranaxeus and Radix Pseudostellariae. Although the JPJY decoction has been used to treat the depression in China, the potential action of its antidepressant has not been well understood. Thus this study was aim to investigate the role of JPJY improve gut microbiota homeostasis in the chronic stress induced depressive mice. Methods: The antidepressant effect of JPJY on chronic unpredictable mild stress (CUMS) mice was evaluated by using sucrose preference test, tail suspension test and forced swim test. Fatigue-like behaviors were evaluated using degree of redness, grip strength test, and exhaustive swimming test. The new object recognition test was used to evaluate cognition performance. Fecal samples were collected and taxonomical analysis of intestinal microbial distribution was conducted with 16S rDNA. Serum level of GABA was measured using high performance liquid chromatography (HPLC). The expression of GluR1 and p-Tau protein in the hippocampus was determined using Western blotting. Results: The dose of 9.2 g/kg JPJY produced antidepressant-like effects. JPJY and its major components also modulated gut microbiota diversity in the CUMS mice. Serum level of GABA and the expressions of hippocampal GluR1 and p-Tau were reversed after the administration of JPJY in CUMS mice. Conclusion: JPJY regulates gut microbiota to produce antidepressant-like effect and improve cognition deficit in depressive mice while its molecular mechanism possibly be enhanced NR1 and Tau expression in hippocampus and increased GABA in serum.